EVTux: A Linux Distribution to the Disciplinary Area of EVT and Arts - Rodrigues, José Alberto (2012)
EVTux is a Linux distribution that is based on the research work we have developed regarding the integration of digital tools in the disciplinary area of Visual Arts and Technology Education. After eighteen months of study and project development carried out by a group of around ninety collaborators, all teachers of this curricular subject, nearly four hundred and thirty digital tools that can be used in the context of Visual Arts and Technology Education were listed. On completion of the listing, cataloging and categorization of the tools was conducted taking into consideration the contents and exploration areas of the subject area. EVTux offers all the applications for Linux already preinstalled. The digital tools that require no installation and run directly from the Web are also integrated in the browser. In addition, there are more than three hundred and fifty manuals for assistance in the use of these tools.EVTux is now available and presents itself as a powerful resource that aggregates all the work of EVTdigital and may become the tool of reference for teachers of this curricular area and Arts for use in the context of their classrooms.Keywords:; ; ; ; .